2009
DOI: 10.1007/s00268-008-9870-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nodal Metastasis and Recurrence Among Patients with Papillary Thyroid Microcarcinoma: Differences in Clinical Relevance Between Nonincidental and Incidental Tumors

Abstract: Several PMCs presented with risk-free clinical courses. Some nonincidental tumors had a more aggressive behavior and a tendency to recurrence. In these cases, early detection and aggressive treatment are mandatory as for conventional PTC according to risk stratification and cancer stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 49 publications
4
67
2
Order By: Relevance
“…Given that CLNM is among the most significant risk factors in predicting locoregional recurrences (4,8,9), the American Thyroid Association (ATA) strongly recommends therapeutic central neck dissection in PTMCs with evidence of CLNM (10). However, diagnosing CLNM only through preoperative imaging is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that CLNM is among the most significant risk factors in predicting locoregional recurrences (4,8,9), the American Thyroid Association (ATA) strongly recommends therapeutic central neck dissection in PTMCs with evidence of CLNM (10). However, diagnosing CLNM only through preoperative imaging is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Given that central neck lymph node metastasis (CLNM) is the most significant risk factor in predicting locoregional recurrences (4,8,9), therapeutic central neck dissection is necessary if CLNM is detected in preoperative examination (10). However, whether prophylactic central neck lymph node dissection (CLND) improves survival rate and prognosis in patients without confirmed CLNM in preoperative examination is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In this study it was 21% (147/709). Pisanu et al (2009) reported 149 cases of tiny PTC, in which there were 73 cases of incidental groups, non-episodic 76 cases, average tumor diameters of two groups were 4.2mm and 7.5mm. To date, detailed studies of the biologic behaviors of IPC have not been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonpalpable nodules have the same risk of malignancy as palpable nodules (Hagag et al, 1998;Lin et al, 2005;Pang and Chen, 2007). The incidence of thyroid carcinoma, which is diagnosed via the surgery for benign thyroid disease or postoperative pathology, also have showed a clear upward trend in recent years (Pang and Chen, 2007;Alevizaki et al, 2009;Pisanu et al, 2009;Lombardi et al, 2010). It is reported that the ratio of multiple nodular goiter with malignant tumors about 4% -17% (Koh and Chang, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation